Where are the mothers? Interrogating maternal mortality as a violation of the rights to life and health : a Nigerian and Ethiopian perspective - Hammad, Salah (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr. Salah Hammad, Faculty of Law, Addis Ababa University, Addis